Baseline data for distribution of contaminants by natural disasters: results from a residential Houston neighborhood during Hurricane Harvey flooding. Issue 11 (November 2019) - Bera, G.; Camargo, K.; Sericano, J.L.; Liu, Y.; Sweet, S.T.; Horney, J.; Jun, M.; Chiu, W.; Rusyn, I.; Wade, T.L.; Knap, A.H.
Abstract: Hurricane Harvey made landfall in Texas August 25, 2017, bringing massive rains and flooding that impacted soils in a residential neighborhood in East Houston. Trace elements, organochlorine pesticides, polycyclic aromatic hydrocarbons (PAHs), polybrominated diphenyl ether fire retardants (PBDEs) and polychlorinated biphenyls (PCBs) were determined in 24 soil samples. The highest concentrations found in soils were total PAHs, which ranged from 1, 310 μg/kg to 85, 700 μg/kg with a mean of 12, 600 μg/kg. Analysis of specific PAH ratios indicate the source of the PAHs were dominated by pyrogenic rather than petrogenic sources. Chlordanes were detectable in the area where the likely local source is for ant control. The trace metal concentrations were below any environmental health concern concentrations but As, Cd, Hg, Pb, Se, Ag, Zn were enriched over the crustal abundance. While Hurricane Harvey was responsible for the redistribution of many contaminants, the large volume of rain and floodwater likely transported contaminants from the land areas and into the Houston Ship Channel and Galveston Bay. The findings from this study will serve as baseline data for determining the mobilization of contaminants caused by natural disasters.